2022
DOI: 10.1038/s41420-022-01231-x
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP35 stabilizes BRPF1 to activate mevalonate (MVA) metabolism during prostate tumorigenesis

Abstract: The mutual interplay between epigenetic modifications and metabolic rewiring contributes to malignant features of prostate adenocarcinoma (PRAD). This study aimed to uncover the biological roles of deubiquitylase USP35 in PRAD and find effective epigenetic or metabolic targets. Bioinformatic tools or methods revealed that USP35 is upregulated in PRAD samples and correlates with inferior prognosis. The in vitro and in vivo assays suggested that USP35 could enhance malignant features of PRAD cells. Mechanistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…USP35 influences multiple biological functions, such as mitosis, ER stress-induced apoptosis, cisplatin-induced apoptosis, ferroptosis, mevalonate metabolism, cell proliferation, and the STING signaling pathway, by deubiquitinating various target substrates, including Aurora B [30], RRBP1 [31], BIRC3 [32], ferroportin [33], BRPF1 [38], estrogen receptor α [39], and STING [34]. However, the role of USP35 in EMT and tumor metastasis has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…USP35 influences multiple biological functions, such as mitosis, ER stress-induced apoptosis, cisplatin-induced apoptosis, ferroptosis, mevalonate metabolism, cell proliferation, and the STING signaling pathway, by deubiquitinating various target substrates, including Aurora B [30], RRBP1 [31], BIRC3 [32], ferroportin [33], BRPF1 [38], estrogen receptor α [39], and STING [34]. However, the role of USP35 in EMT and tumor metastasis has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, somatic BRPF1 mutations have been identified in sonic hedgehog medulloblastoma [ 57 ] and pediatric cancers [ 58 ]. Although there are not many studies on the function of BRPFs in cancer, its significance has been noted in liver cancer [ 59 ], lower-grade gliomas [ 60 ] and PCa [ 61 ]. Gene ablation or pharmacological inactivation of BRPF1 significantly attenuated HCC cell growth in vitro and in vivo [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al identified BRPF1 as a potential drug target in lower-grade gliomas, as inhibiting BRPF1 function or silencing BRPF1 was found to reduce glioma cell proliferation and colony formation [ 60 ]. Lin et al showed the USP35/BRPF1 axis promoted malignant features of PCa by activating the mevalonate pathway [ 61 ]. Although the oncogenic role of BRPF1 was clearly demonstrated in these studies, its relationship with drug resistance has not been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cheng et al [ 91 ] demonstrated that BRPF1 might serve as a druggable target in liver cancer, where BRPF1 was involved in the regulation of cell cycle progression, senescence, and cancer stemness of hepatocellular carcinoma. In prostate tumors, accumulated BRPF1 protein accelerated the cell growth, stem-like properties, and migration of cancer cells, further supporting the role of BRPF1 in cancer stemness [ 92 ]. As for BRPF2 and BRPF3, little is known about their engagement in cancer development and progression, leaving an open question of whether they exert similar activity as BRPF1 in maintaining cancer stem cell-like phenotype.…”
Section: Several Brd Family Members Play a Fundamental Role In Cancer...mentioning
confidence: 97%